A Sistem Informasi Manajemen Perancangan Monitoring Kinerja Teknisi Servis Berbasis Website Dengan Metode Rational Unified Process (RUP) - Setiawan, Andre Stenki; Sihotang, Fransiska Prihatini (Jurnal Teknologi Sistem Informasi, 2022)
Current technological advances have provided enormous benefits for a company, especially in carrying out operational activities and data management such as laptop spare parts, technician performance and repair status. This system was developed at a company that receives computer, printer and other electronic service services that can provide detailed information related to damage then the damage will be processed by a technician to carry out a repair analysis, the information will be confirmed to the user through the admin, if the user agree, the repair will be continued at the stated price. All these reports will be linked to the system manager. This system was developed using the Rational Unified Process (RUP) methodology such as use case diagrams, sequential diagrams, and class diagrams of the PHP programming language with Laravel Framework and MySQL database. The results of making this system can help companies run their service center activities better and provide information related to repairing damage to managers more efficiently.